High-performance PTCR ceramics with extremely low resistivity for multilayer chip thermistor application. Issue 5 (1st April 2020) - Yan, Liang; Fu, Qiuyun; Humayun, Muhammad; Zhou, Dongxiang; Wang, Mei; Wang, Geng; Gao, Xiaoyun; Zheng, Zhiping; Luo, Wei
Abstract: It is a great challenge to prepare chip thermistors with high positive temperature coefficient of resistivity (PTCR) jump and simultaneously low room temperature resistivity by reduction-reoxidation method. In this work, the influence of Mn doping on Ba0.996 La0.004 (Bi0.5 Na0.5 )0.003 TiO3 based chip thermistors were carefully investigated and Mn doping was proved to be an effective way in preparation of high-performance PTCR ceramics with low resistivity. The results showed that Mn can't create a high enough potential barrier in un-oxidized samples but can obviously increase the value of potential barrier height after reoxidation. The trap activation of Mn d states near Curie point helps to reduce room temperature resistivity and increase PTCR jump in reoxidized samples. As a result, samples with extremely low resistivity and high PTCR jump of 10 3.4 were reported for the first time.